Mosque Revitalization as a Character-Building Center for Youth Based on Minangkabau Local Wisdom - Hamzah Irfanda Fanda; Aldi Saputra; Syifa Ullinnas; Farida Ariani (Jurnal Pengabdian Masyarakat Inovatif, 2026)
The rapid development of globalization and digital technology has significantly influenced the character and social behavior of young generations, particularly in weakening religious awareness, social ethics, and cultural identity. In the context of Minangkabau society, these challenges have become increasingly concerning as many young people are gradually disconnected from mosque-centered activities and local cultural values rooted in the philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah.” Historically, mosques in Minangkabau function not only as places of worship but also as centers for moral education, social interaction, and cultural transmission. Therefore, this community service activity aimed to revitalize the role of Masjid Raya Padusunan Heritage Mosque in strengthening youth character through the integration of Islamic values and Minangkabau local wisdom. This activity was conducted on March 12, 2026, at Masjid Raya Padusunan, Pariaman City, using a participatory-educative approach. The program involved youth mentoring, interactive discussions, cultural reflection sessions, and character-building activities based on local wisdom values. Data were collected through observation, documentation, interviews, and participant response questionnaires. The results indicated a significant increase in participants’ understanding of the mosque’s role as a center for character development and cultural preservation. Approximately 85% of participants demonstrated improved awareness regarding the importance of Islamic and cultural values in everyday life, while 78% expressed motivation to become more actively involved in mosque activities. These findings suggest that revitalizing the social and educational functions of heritage mosques through culturally contextual approaches can effectively strengthen youth character and reinforce local identity amidst the challenges of globalization.